2014
DOI: 10.1002/oby.20895
|View full text |Cite
|
Sign up to set email alerts
|

Changes in food choice during a successful weight loss trial in overweight and obese postpartum women

Abstract: Objective: To examine changes in intake across food groups during a weight loss trial that produced significant and sustainable weight loss in lactating women receiving dietary treatment. Methods: At 10-14 wk postpartum, 61 overweight and obese lactating Swedish women were randomized to a 12-wk dietary (D), exercise (E), combined (DE), or control (C) treatment. Food intake was assessed by 4-d weighed diet records which were used to examine changes in intake across seven food groups from baseline to 12 wk and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…The postpartum period has been associated with an increase in food intake and a decrease in physical activity level (PAL) (7)(8)(9) . Breast-feeding also has been shown to be positively associated with improved dietary quality in overweight and obese women (10,11) . However, no differences in PAL have been observed between women who never initiated breast-feeding and those who practise exclusive breast-feeding (EBF) (12) .…”
mentioning
confidence: 99%
“…The postpartum period has been associated with an increase in food intake and a decrease in physical activity level (PAL) (7)(8)(9) . Breast-feeding also has been shown to be positively associated with improved dietary quality in overweight and obese women (10,11) . However, no differences in PAL have been observed between women who never initiated breast-feeding and those who practise exclusive breast-feeding (EBF) (12) .…”
mentioning
confidence: 99%
“…This diary is a valid instrument for estimating nutrition intake and a beneficial tool for self-monitoring of dietary intake. It has been proved and performed in numerous nutrition researches [ 32 – 34 ]. Moreover, minimization will be conducted as a random procedure in this trial, avoiding possible confounding factors such as different obesity levels, gender, and age.…”
Section: Discussionmentioning
confidence: 99%
“…The lifestyle modification treatment was designed by experienced nutritionists, and the treatment protocol was established before the study began. Firstly, each patient’s lifestyle, including daily nutrient intake and exercise habit, will be collected using a dietary questionnaire [ 33 , 34 ] and analyzed by a nutritionist at the beginning of the study. A face-to-face nutritional consultation will be subsequently arranged for each patient, in order to tailor an individualized lifestyle treatment.…”
Section: Interventionmentioning
confidence: 99%
“…25 This weight loss implied a caloric reduction as well as changes in the diet composition, with lower proportions of fat and sucrose intake and higher content of carbohydrates and fibers complexes. 28 Huseinovic et al 32 observed that reducing and/or replacing high-calorie food such as snacks and soft drinks for vegetable consumption significantly reduced postpartum weight. Increased protein intake has also been associated with postpartum weight loss.…”
Section: Dietmentioning
confidence: 99%